Relación del colesterol total y triglicéridos con el índice de masa corporal en pacientes adultos atendidos en el Hospital Gustavo Lanatta Lujan – Bagua, 2017 – 2018 - García Rodríguez, Marcos Daniel (2019)
The relationship between cholesterol and triglyceride levels with BMI was determined in adult patients treated at the Gustavo Lanatta Lujan Hospital in the city of Bagua, Amazonas region in the period 2017 - 2018. For the determination of the body mass index, had to weigh and carve each participant, determined the weight and height. For the determination of total cholesterol and triglycerides was made according to the technique proposed by the manufacturer of Stambio reagent. The bivariate analysis to evaluate the association between cholesterol and triglyceridemia and the body mass index was performed using the chi square test, and the strength of association will be measured by prevalence (PR) and its respective confidence interval. 95%. It was found that 40.1% of patients presented pathological total cholesterol; 59% pathological triglycerides, while with respect to the body mass index 75.8% was pathological. There was no association between hypercholesterolemia and BMI, but there was a positive association between obesity and overweight with hypertriglyceridemia (p = 0.001). Likewise, people older than 40 years did not present an association with any level of body mass index - BMI (p = 0.308). We conclude that there is no significant statistical relationship between hypercholesterolemia and BMI and whether there is a statistically significant relationship between obesity and overweight with hypertriglyceridemia, while people older than 40 years did not present a statistically significant relationship with any level of BMI.